The enhanced performance of piezoelectric nanogenerator via suppressing screening effect with Au particles/ZnO nanoarrays Schottky junction - Lu, Shengnan; Liao, Qingliang; Qi, Junjie; Liu, Shuo; Liu, Yichong; Liang, Qijie; Zhang, Guangjie; Zhang, Yue (Nano research, 2016)
This paper describes a novel strategy to weaken the piezopotential screening effect by forming Schottky junctions on the ZnO surface through the introduction of Au particles onto the surface. With this approach, the piezoelectric-energyconversion performance was greatly enhanced. The output voltage and current density of the Au@ZnO nanoarray-based piezoelectric nanogenerator reached 2 V and 1 μA/cm^2, respectively, 10 times higher than the output of pristine ZnO nanoarray-based piezoelectric nanogenerators. We attribute this enhancement to dramatic suppression of the screening effect due to the decreased carrier concentration, as determined by scanning Kelvin probe microscope measurements and impedance analysis. The lowered capacitance of the Au@ZnO nanoarraybased piezoelectric nanogenerator also contributes to the improved output. This work provides a novel method to enhance the performance of piezoelectric nanogenerators and possibly extends to piezotronics and piezophototronics.